Characterisation of the treatment provided for children with unilateral hearing loss - Patel, Roshni; Hoare, Derek J.; Willis, Karen R.; Tabraiz, Shammas; Bateman, Paul K.; Thornton, Sally K. (Frontiers in Pediatrics, 2023)
Background: Children with unilateral hearing loss (UHL) are an understudied population, with limited data to inform management guidelines. They are a disparate population concerning aetiology and degree of hearing loss hence device choice and use vary. There is a paucity of data on support provided and concerns raised by children with UHL. There is a funding gap in healthcare provision for children with UHL in the UK, where genetic screening, support services and devices are not consistently provided. Methods: A cohort study collecting longitudinal data for 63 children with permanent congenital confirmed UHL in a large tertiary centre (2002-2019). Data were taken from their diagnostic auditory brainstem responses and two most recent hearing assessments. Descriptors recorded include aetiology, age of device trials, when and which devices are used, concerns reported, and support provided. Results: Most (45/63, 71%) children trialled a device, a bone conduction device (44%), a contralateral routing of signal aid (36%) or a hearing aid (20%). Eighty percent (36/45) of children indicated they wore their device all day or every day in school. First fitting of devices was later than previously reported however, recent cases were fit earlier. Few children reported rarely wearing their device. Their reasons for reduced wear included bullying, feedback, and device discomfort. Only one child reported the device did not help with their hearing. Most children reported no concerns, however, the concerns reported included five with hearing aid difficulties, five with speech issues, four with no perceived improvement in hearing, three facing self-image or bullying issues and one child struggled socially. Where concerns were raised more than half were by the school/teachers. Of the 51 children who were referred to support services, 73% received their intended support with no issue. Conclusion: Most children with UHL reported they use their device in school. In lieu of available data, it will be vital to support families and clinicians in understanding devices most used, where they are used and why they are not used. Considering the reasons for cessation of regular device use counselling and support services are vital for families of children with UHL.